2010
DOI: 10.1071/sh09068
|View full text |Cite
|
Sign up to set email alerts
|

Misclassification bias: diversity in conceptualisations about having 'had sex'

Abstract: These findings highlight the need to use behaviour-specific terminology in sexual history taking, sex research, sexual health promotion and sex education. Researchers, educators and medical practitioners should exercise caution and not assume that their own definitions of having 'had sex' are shared by their research participants or patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 14 publications
(16 reference statements)
3
55
1
Order By: Relevance
“…Consistent with previous research with predominantly heterosexual and mostly college samples (Byers et al, 2009;Carpenter, 2001;Gute et al, 2008;Pitts & Rahman, 2001;Randall & Byers, 2003;Richters & Song, 1999;Sanders & Reinisch, 1999;Sanders et al, 2010), penile-vaginal intercourse was the most frequently included item within the behavioral definition of having sex with a man in this sample of WSWM. In contrast to penile-vaginal intercourse, the percentage of participants who indicated that they would have indicated that they had sex if they engaged in fellatio in the present study was considerably higher than the percentage of participants who reported that fellatio was "having sex" in previous research with primarily heterosexual participants (Byers et al, 2009;Carpenter, 2001;Gute et al, 2008;Pitts & Rahman, 2001;Randall & Byers, 2003;Richters & Song, 1999;Sanders & Reinisch, 1999;Sanders et al, 2010). However, the diversity in their definitions is consistent with the few other studies that have examined sexual orientation as a factor in behavioral definitions of having sex Horowitz & Spicer, 2013;Richters & Song, 1999).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with previous research with predominantly heterosexual and mostly college samples (Byers et al, 2009;Carpenter, 2001;Gute et al, 2008;Pitts & Rahman, 2001;Randall & Byers, 2003;Richters & Song, 1999;Sanders & Reinisch, 1999;Sanders et al, 2010), penile-vaginal intercourse was the most frequently included item within the behavioral definition of having sex with a man in this sample of WSWM. In contrast to penile-vaginal intercourse, the percentage of participants who indicated that they would have indicated that they had sex if they engaged in fellatio in the present study was considerably higher than the percentage of participants who reported that fellatio was "having sex" in previous research with primarily heterosexual participants (Byers et al, 2009;Carpenter, 2001;Gute et al, 2008;Pitts & Rahman, 2001;Randall & Byers, 2003;Richters & Song, 1999;Sanders & Reinisch, 1999;Sanders et al, 2010). However, the diversity in their definitions is consistent with the few other studies that have examined sexual orientation as a factor in behavioral definitions of having sex Horowitz & Spicer, 2013;Richters & Song, 1999).…”
Section: Discussionsupporting
confidence: 89%
“…In comparison, fewer than 40% of the participants indicated that they would say they had sex with a partner if they engaged in oral-genital contact, and fewer than 20% of the participants indicated that they would include kissing, breast stimulation, or digital-vaginal stimulation within their behavioral definition of having sex. This is consistent with findings from other research that has identified similar variation in participants' behavioral definitions of having sex (Bogart, Cecil, Wagstaff, Pinkerton, & Abramson, 2000;Byers, Henderson, & Hobson, 2009;Carpenter, 2001;Gute, Eshbaugh, & Wiersma, 2008;Pitts & Rahman, 2001;Randall & Byers, 2003;Richters & Song, 1999;Sanders et al, 2010). Although age is related to the likelihood of including individual behaviors within a participant's behavioral definition of having sex, penile intercourse (the insertion of the penis into the vagina or anus) is consistently among the behaviors most likely to be included regardless of participant age .…”
supporting
confidence: 87%
See 1 more Smart Citation
“…First, "sex" was not explicitly defined for participants as a particular type of sexual experience (e.g., penetrative vaginal intercourse). As previous work has shown (Sanders, Hill, Yarber, Graham, Crosby, & Milhausen, 2010), this presents a limitation to our understanding of what types of sexual behaviors participants may have been reporting on. Another limitation was that we did not explicitly define "childhood" for our participants.…”
Section: Limitations and Future Directionsmentioning
confidence: 86%
“…Horowitz & Spicer, 2013). This hierarchy persists, even where percentages vary as a function of, for example, culture (e.g., Pitts & Rahman, 2001; Randall & Byers, 2003), age (e.g., Sanders et al, 2010), target (e.g., Bogart, Cecil, Wagstaff, Pinkerton, & Abramson, 2000), or context (e.g., Trotter & Alderson, 2007). Qualitative research tends to support the definitional hierarchy (e.g., Carpenter, 2001; Mehta, Sunner, Head, Crosby, & Shrier, 2011).…”
Section: Introductionmentioning
confidence: 99%